Body Mass Index and Tooth Loss: An Epidemiological Study in a Sample of Suburban South Indian Population - Parthasarathy Natarajan; Minati Choudhury; Madhan Kumar Seenivasan; Karthigeyan Jeyapalan; Shanmuganathan Natarajan; Anand Kumar Vaidhyanathan (Wolters Kluwer Medknow Publications, 2019)
Aim: This study evaluated the relationship between missing posterior teeth and body mass index with regard to age and socioeconomic state in a sample of the suburban south Indian population. Materials and Methods: The 500 individuals of both males and females aged 40 years and older with missing posterior teeth and not rehabilitated with any prosthesis were gone through a clinical history, intraoral examination, and anthropometric measurement to get information regarding age, sex, socioeconomic status, missing posterior teeth, and body mass index (BMI). Subjects were divided into five groups according to BMI (underweight > 18.5kg/m2, normal weight 18.5-23kg/m2, overweight 23-25kg/m2, obese without surgery 25-32.5kg/m2, obese with surgery < 32.5kg/m2). Multivariate logistic regression was used to adjust data according to age, sex, number of missing posterior teeth, and socioeconomic status. Results: People with a higher number of tooth loss were more obese. Females with high tooth loss were found to be more obese than male. Low socioeconomic group obese female had significantly higher tooth loss than any other group. No significant relation between age and obesity was found with regard to tooth loss. Conclusion: The BMI and tooth loss are interrelated. Management of obesity and tooth loss can help to maintain the overall health status.